Al-Ghazali and the Golden Rule: Ethics of Reciprocity in the Works of a Muslim Sage. (3rd April 2017) - Parrott, Justin
ABSTRACT: The golden rule ("do unto others as you would have them do unto you") has become an important focal point in modern interfaith dialogue with Muslims. As an ethical concept, it can be transferred, more or less, intact between different religions and philosophies, with or without the authority of scripture. This article aims to assist interfaith efforts with Muslims by examining the use of the golden rule in the works of 12th century Muslim mystic, ethicist, and theologian Abū Ḥāmid al-Ghazzālī ("Al-Ghazali"). Al-Ghazali is one of the most influential and popular of the classical scholars of Islam, whose impact and appreciation is felt in the East and West, both within Islam and without. He applies the golden rule in various formulations as an axis around which great themes of religion are surrounded: God, purity of heart, justice, compassion, altruistic love, goodwill, human brotherhood, and neighborliness. Four texts are examined with specific attention paid to his most famous work, Iḥyā' 'Ulūm al-Dīn .